Race morphological characteristics and correlation between uphill grade and velocity in ski mountaineering - Sideris, V.; Voutselas, V.; Lazopoulou, V.; Soulas, D.; Papanikolaou, Z.; Kritikos, A. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Ski Mountaineering is relatively new competition event that combines elements from the alpine ski (downhill skiing), cross-country ski (uphill skiing) and mountaineering techniques. Limited research has been done in Ski Mountaineering. Voutselas et al. (2005) showed that velocity at VO2max strongly correlates with athletes' uphill skiing velocity. The main aim of the present study was to examine whether there is a correlation between athletes1 uphill skiing velocity and uphill course grade in Ski Mountaineering. In addition, to identify the uphill course morphological characteristics of Ski Mountaineering Races.